Developing Podcast-Based Learning Media for English Education Among Deaf Students - Yuniarti, Fatma; Pratiwi, Dian; Novianto, Robi (Universitas Hamzanwadi, 2024)
This study addresses the educational challenges faced by deaf students in Indonesia, focusing on developing and implementing a specialised Android-based application,